Tratamiento protésico de un caso de displasia ectodérmica hipohidrótica (2000)
ABSTRACT: Anodontia is an entity associated to diferent kind of síndromes. This article reports the treatment using complete dentures, of a six years child who doesn´t have neither deciduous or permanent dentition, because of an Hypohidrotic Ectodermal Dysplasia. Variations to the conventional technique for complete dentures have been introduced, some of them reported in the literature, and other such a result of either personal and other investigators´research.